The Effectiveness of Spiritual Emotional Freedom Technique in Improving Sleep Quality among Cancer Patients - Lisarni, Linda; Nauli, Fathra Anis; Marthiningsih, Marthiningsih; Huda, Nurul; Pranata, Satriya (Alta Dharma Publisher, 2022)
Introduction: Cancer patients often experience sleep disorders. One of the non-pharmacological treatments that can improve sleep quality is the spiritual, emotional freedom technique (SEFT). Objectives: The study aimed to identify the effectiveness of SEFT on sleep quality among cancer patients. Methods: This research applied a quasi-experiment with a pre-test and post-test approach using a non-equivalent control group design. The total sample of this study was 30 respondents collected by purposive sampling. The sleep quality index questionnaires measured sleep quality. Results: In the pre-test, the average sleep quality score among respondents in the experimental group was 12.33, then became 8.93 after the post-test with a p-value < 0.007. Meanwhile, the pre-test score for sleep quality among respondents in the control group was 13.40, then became 13.20 after the post-test with a p-value of 0.026. Conclusion: it can be concluded that SEFT can improve the sleep quality of cancer patients. Improving the quality of sleep in cancer patients can reduce fatigue, the main side effect of undergoing therapy